The effect of indoor daylight spectrum and intensity on viability of indoor pathogens on different surface materials. (19th July 2022) - Lam, Man In; Vojnits, Kinga; Zhao, Michael; MacNaughton, Piers; Pakpour, Sepideh
Abstract: Built environments play a key role in the transmission of infectious diseases. Ventilation rates, air temperature, and humidity affect airborne transmission while cleaning protocols, material properties and light exposure can influence viability of pathogens on surfaces. We investigated how indoor daylight intensity and spectrum through electrochromic (EC) windows can impact the growth rate and viability of indoor pathogens on different surface materials (polyvinyl chloride [PVC] fabric, polystyrene, and glass) compared to traditional blinds. Results showed that tinted EC windows let in higher energy, shorter wavelength daylight than those with clear window and blind. The growth rates of pathogenic bacteria and fungi were significantly lower in spaces with EC windows compared to blinds: nearly 100% growth rate reduction was observed when EC windows were in their clear state followed by 41%–100% reduction in bacterial growth rate and 26%–42% reduction in fungal growth rate when EC windows were in their darkest tint. Moreover, bacterial viabilities were significantly lower on PVC fabric when they were exposed to indoor light at EC‐tinted window. These findings are deemed fundamental to the design of healthy modern buildings, especially those that encompass sick and vulnerable individuals.